CCL2 Is a Vascular Permeability Factor Inducing CCR2-Dependent Endothelial Retraction during Lung Metastasis - Roblek, Marko; Protsyuk, Darya; Becker, Paul F; Stefanescu, Cristina; Gorzelanny, Christian; Glaus Garzon, Jesus F; Knopfova, Lucia; Heikenwalder, Mathias; Luckow, Bruno; Schneider, Stefan W; Borsig, Lubor (Molecular cancer research, 2019)
Increased levels of the chemokine CCL2 in cancer patients are associated with poor prognosis. Experimental evidence suggests that CCL2 correlates with inflammatory monocyte recruitment and induction of vascular activation, but the functionality remains open. Here, we show that endothelial Ccr2 facilitates pulmonary metastasis using an endothelial-specific Ccr2-deficient mouse model (Ccr2ecKO). Similar levels of circulating monocytes and equal leukocyte recruitment to metastatic lesions of Ccr2ecKO and Ccr2fl/fl littermates were observed. The absence of endothelial Ccr2 strongly reduced pulmonary metastasis, while the primary tumor growth was unaffected. Despite a comparable cytokine milieu in Ccr2ecKO and Ccr2fl/fl littermates the absence of vascular permeability induction was observed only in Ccr2ecKO mice. CCL2 stimulation of pulmonary endothelial cells resulted in increased phosphorylation of MLC2, endothelial cell retraction, and vascular leakiness that was blocked by an addition of a CCR2 inhibitor. These data demonstrate that endothelial CCR2 expression is required for tumor cell extravasation and pulmonary metastasis. IMPLICATIONS: The findings provide mechanistic insight into how CCL2-CCR2 signaling in endothelial cells promotes their activation through myosin light chain phosphorylation, resulting in endothelial retraction and enhanced tumor cell migration and metastasis.
Keywords: Receptors, CCR2; Carcinoma, Lewis Lung; Animals; metastázy nádorů; Mice, Knockout; myši knockoutované; nádory plic; kapilární permeabilita; Mice; Endothelial Cells; myši; lehké řetězce myosinu; pohyb buněk; Myosin Light Chains; chemokin CCL2; karcinom plic Lewisové; Capillary Permeability; Chemokine CCL2; endoteliální buňky; Lung Neoplasms; receptory CCR2; Cell Movement; zvířata; Mice, Inbred C57BL; Neoplasm Metastasis; myši inbrední C57BL